2006
DOI: 10.1063/1.2405890
|View full text |Cite
|
Sign up to set email alerts
|

Intersubband transition in narrow GaInNAs∕GaAs quantum wells

Abstract: The authors report on experimental results of intersubband absorption in a set of Ga0.77In0.23N0.01As0.99∕GaAs quantum well structures with different well widths from 2.6to4.4nm. Due to the peculiar conduction band dispersion, the observed intersubband transition energy is quite insensitive to the well width for these narrow wells. The observed intersubband resonance positions are in good agreement with a model calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Recent works, dealing with intersubband absorption in dilute nitrides, reported on contradicting selection rules for these transitions, i.e. TM or TE dominant polarization induced transition, and insensitivity to QW width [1][2][3][4]. Here we report on a new experimental evidence of an unpolarized intersubband photocurrent measured in Te doped GaInAsN/GaAlAs quantum well infrared photodetector.…”
mentioning
confidence: 81%
“…Recent works, dealing with intersubband absorption in dilute nitrides, reported on contradicting selection rules for these transitions, i.e. TM or TE dominant polarization induced transition, and insensitivity to QW width [1][2][3][4]. Here we report on a new experimental evidence of an unpolarized intersubband photocurrent measured in Te doped GaInAsN/GaAlAs quantum well infrared photodetector.…”
mentioning
confidence: 81%
“…In recent years, a number of investigations have been published on the intersubband transitions (ISBTs) in the conduction band of dilute N-containing QWs. [17][18][19][20][21][22][23] For example, Duboz et al 17 reported the observation of ISBTs in n-type GaInNAs/GaAs multiple quantum wells (MQWs) for the first time. Luna et al 18 demonstrated a double-barrier GaAsN/AlAs/AlGaAs QW infrared photo-detector, which operates in the near infrared.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to the number of experimental investigations, very limited amount of theoretical work has been done for the ISBTs in the dilute N-containing QWs. [20][21][22][23] The theoretical analyses were mostly based on simplified two-band, three-band k · p, ten-band k · p or analytical models based on the band-anticrossing (BAC) theory.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These are attributed to the highly localized nature of perturbations induced by N although the exact physical mechanism behind them remains the subject of ongoing debates. [11][12][13][14][15][16] For example, Duboz et al 11 reported the observation of ISBTs in n-type InGaAsN/GaAs multiple quantum wells ͑MQWs͒ for the first time. 4 The dilute N materials can also be used for intersubband transition ͑ISBT͒ based optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing N composition x, the In 1−y Ga y As 1−x N x / ͑Al, Ga͒As QWs can allow the photons with much shorter wavelengths to be absorbed through ISBTs compared to the In 1−y Ga y As/ ͑Al, Ga͒As structure due to the much larger conduction-band discontinuity. Liu et al 15 measured the ISBTs in a set of In 0.77 Ga 0.23 As 0.99 N 0.01 / GaAs MQWs with narrow well widths and found that the transition energy was very insensitive to the well width. On the other hand, the introduction of N can compensate the lattice mismatch caused by In.…”
Section: Introductionmentioning
confidence: 99%